Business data networks and telecommunications. - Panko, Raymond R., ....- (Upper Saddle River : Pearson, 2009)
Panko teaches students about the technologies that are being used in the marketplace. This text covers market-driven content such as wireless LANs, security and network management, TCP/IP, and application layers. This text would be suitable for business professionals looking for the most recent developments in data communications and networking.
Keywords: Digitale netwerktheorie; Netwerktheorie; Telecommunicatie